Herbal preparations for uterine fibroids - Liu, Jian Ping (2009)
BACKGROUND: Uterine fibroids are the most common non-malignant growths in women of childbearing age. They are associated with heavy menstrual bleeding and subfertility. Herbal preparations are commonly used as alternatives to surgical procedures. OBJECTIVES: To assess the benefits and risks of herbal preparations for uterine fibroids. SEARCH STRATEGY: Authors searched following electronic databases: the Trials Registers of the Cochrane Menstrual Disorders and Subfertility Group and the Cochrane Complementary Medicine Field, the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library 2008, Issue 3), MEDLINE, EMBASE, the Chinese Biomedical Database, the Traditional Chinese Medical Literature Analysis and Retrieval System (TCMLARS), AMED, and LILACS. The searches ended on 31st December 2008. SELECTION CRITERIA: Randomised controlled trials comparing herbal preparations with no intervention, placebo, medical treatment or surgical procedures in women with uterine fibroids. We also included trials of herbal preparations with or without conventional therapy. DATA COLLECTION AND ANALYSIS: Two review authors collected data independently. We assessed trial risk of bias according to our methodological criteria. We presented dichotomous data as risk ratios (RR) and continuous outcomes as mean difference (MD), both with 95% confidence intervals (CI). MAIN RESULTS: We included two randomised trials (involved 150 women) with clear description of randomisation methods. The methodological risk of bias of the trials varied. There were variations in the tested herbal preparations, and the treatment duration was six months. The outcomes available were not the primary outcomes selected for this review, such as symptom relief or the need for surgical treatment; trials mainly reported outcomes in terms of shrinkage of the fibroids. Compared with mifepristone, Huoxue Sanjie decoction showed no significant difference in the disappearance of uterine fibroids, number of patients with shrinking of uterine fibroids or average volume of uterine fibroids, but less effective than mifepristone on reducing average size of uterus (mean difference 23.23 cm(3), 95% confidence interval 17.85 to 28.61). There was no significant difference between Nona Roguy herbal product and GnRH agonist in average volume of uterine fibroids or size of uterus. No serious adverse effects from herbal preparations was reported. AUTHORS’ CONCLUSIONS: Current evidence does not support or refute the use of herbal preparations for treatment of uterine fibroids due to insufficient studies of large sample and high quality. Further high quality trials evaluating clinically relevant outcomes are warranted.